The framed Rose : non-normative lives in the Litonovela of Raul Cruz (TEL Tempo, Espaço e Linguagem, 2021)
In an initial analysis of Litonovela by Curitiban artist Raul Cruz, this article aims to discuss the possibility of The Rose, a sequence of lithogravure produced in the 1980s, being understood as “a testimony of his time”, according to Didier Quella-Guyot’s perspective to observe comics. To do so, I rely on Judith Butler's theories about framing as a preservation mechanism of certain ways of life at the expense of others. Furthermore, I adopt the author's studies regarding the performativity of gender, sexuality and identity.